Bismuth trioxide / copper-zinc-tin-sulfur composite photocatalyst, preparation method thereof and application of bismuth trioxide / copper-zinc-tin-sulfur composite photocatalyst in photodegradation
Porous mesh BO was synthesized by microwave solvent thermal method and CZTS nanosheets were grown thereon, and BO/CZTS composite photocatalyst was prepared, which solved the problem of δ-BO synthesis in the prior art, achieved efficient photocatalytic degradation effect and improved the reusable performance of the catalyst.
Patent Information
- Application Number
- CN202411983205.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, the synthesis method of two-dimensional δ-BO is mainly a solvent method, which consumes a long time and is not very active. The positive conduction band energy level leads to low charge separation efficiency and low light energy utilization.
Porous mesh BO was synthesized by microwave solvothermal method, and copper-zinc-tin-sulfur (CZTS) nanosheets were grown on BO by surface modification and microwave solvothermal method to prepare bismuth trioxide/copper-zinc-tin-sulfur (BO/CZTS) composite photocatalyst.
The activity and reaction efficiency of the photocatalyst are improved, the charge separation and transmission capacity is enhanced, and the problems of low activity, long synthesis and high energy consumption of a single BO photocatalyst are solved. The reusable performance of the catalyst is improved through hydrogel embedding.
Smart Images

Figure CN119869558A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nano materials and preparation thereof, and specifically relates to a bismuth trioxide / copper zinc tin sulfur composite photocatalyst and a preparation method thereof and application in photodegradation. Background Art
[0002] In view of the increasingly serious water pollution problem, photocatalytic oxidation has become the greenest and most efficient method for superoxidation of organic pollutants, and the choice of photocatalyst is the key. Bismuth-based semiconductor photocatalysts have good chemical stability, controllable morphology and unique electronic band structure under visible light irradiation. Because its valence band is formed by the hybridization of O 2p orbital and Bi6s orbital, the distortion of Bi 6s orbital can lead to obvious overlap of O 2p orbital and Bi 6s orbital, which is conducive to increasing the mobility of carriers and reducing the band gap. Bismuth trioxide (BO) is one of the simplest bismuth-based photocatalysts. It is considered to be an attractive photocatalytic material because of its inherent properties such as non-toxicity, high thermal stability and high conductivity. BO has six crystal phases (α, β, γ, δ, ε and ω), among which the δ type with cubic structure has the best conductivity among oxide materials and has strong oxidation activity due to its lower valence band edge. In addition to the type of material, morphology also plays an important role in charge separation and transport. Two-dimensional nanomaterials have large specific surface area, significant quantum effects, and abundant photocatalytic active sites, making them an attractive class of photocatalytic materials.
[0003] At present, the synthesis method of two-dimensional δ-BO is mainly solvent method. However, the solvothermal reaction takes too long. Therefore, it is of great significance to find an efficient and convenient synthesis method. In addition, the conduction band energy level of δ-BO material is relatively positive, which is not enough to reduce the adsorbed O2 to form ·O2 - , which makes the photogenerated electron-hole pairs easy to recombine and leads to low charge separation efficiency. At the same time, due to the wide band gap of BO, it can only absorb high-energy ultraviolet light, which reduces its light energy utilization rate, thereby affecting its photocatalytic efficiency and limiting its application potential. Summary of the invention
[0004] The purpose of the present invention is to provide a bismuth trioxide / copper zinc tin sulfur (BO / CZTS) composite photocatalyst and a preparation method thereof. The present invention first synthesizes a porous mesh BO by microwave solvothermal method, and after surface modification, further grows copper zinc tin sulfur (CZTS) on BO by microwave solvothermal method to prepare a BO / CZTS composite photocatalyst. The preparation method provided by the present invention solves the problems of low activity, long synthesis time and high energy consumption of a single BO photocatalyst.
[0005] Another object of the present invention is to provide an application of BO / CZTS composite photocatalyst in photodegradation. The present invention utilizes hydrogel to embed BO / CZTS to prepare macroscopically large gel balls as photocatalysts, thereby improving the reusability of the catalyst.
[0006] The specific technical solutions of the present invention are as follows:
[0007] The preparation method of bismuth trioxide / copper zinc tin sulfur composite photocatalyst comprises the following steps:
[0008] 1) Preparation of porous network BO by microwave solvothermal reaction;
[0009] 2) Modification of porous mesh BO by surface modifier;
[0010] 3) adding a copper source and a ligand into an organic solvent, then adding a zinc source, a tin source and a sulfur source, stirring evenly, and finally adding the surface-modified BO, transferring the obtained mixed dispersion into an autoclave for microwave solvent thermal reaction, and then washing and drying to obtain a BO / CZTS composite photocatalyst.
[0011] In step 1), the method for preparing porous mesh BO by microwave solvent thermal reaction is:
[0012] The bismuth salt is dissolved in an organic solvent and stirred evenly; the obtained mixed solution is transferred to an autoclave for microwave solvent thermal reaction, and then washed and dried to obtain a porous mesh BO.
[0013] In step 1), the bismuth salt is Bi(NO3)3·5H2O; its concentration in the organic solvent is 0.03-0.06 mol / L, preferably 0.046 mol / L; the organic solvent is a mixed solution of ethylene glycol and acetone, and the volume ratio of ethylene glycol to acetone is 1:2; the microwave power of the microwave solvent thermal reaction is 200-1000 W, preferably 800 W; the system pressure is 2-3 MPa, preferably 2 MPa; the reaction temperature is 140-180°C, preferably 160°C; the reaction time is 5-40 min, preferably 20 min.
[0014] In step 2), the method of modifying the porous mesh BO with the surface modifier is specifically as follows: dispersing the porous mesh BO in deionized water, adding the surface modifier, stirring, and washing to obtain the surface-modified BO;
[0015] In step 2), the concentration of BO in deionized water is 1-10 mg / mL, preferably 6.7 mg / mL; the surface modifier is selected from ethanethiol, 2-mercaptoacetic acid, 3-mercaptopropionic acid, preferably 3-mercaptopropionic acid; the amount ratio of the surface modifier to deionized water is 1-10 μL / mL, preferably 3.3 μL / mL; the surface modifier is added and stirred, and the stirring time is 1-12 hours, preferably 6 hours; the cleaning refers to washing with water and DMF once each and then setting aside.
[0016] In step 3), the copper source is CuCl2·2H2O or Cu(CH3COO)2·H2O, preferably CuCl2·2H2O; the concentration of the copper source in the organic solvent is 0.001-0.002 mol / L, preferably 0.00128 mol / L;
[0017] The molar ratio of the copper source, zinc source, tin source and sulfur source is 5-8:2-5:2-5:15-20; preferably 8:4:4:18;
[0018] In step 3), the ligand is polyvinyl pyrrolidone (PVP), the mass of the ligand is 15-20 times the mass of the copper source, preferably 18 times; the zinc source is ZnCl2 or Zn(CH3COO)2, preferably ZnCl2; the tin source is SnCl4·5H2O; the sulfur source is thiourea; the organic solvent is N,N-dimethylformamide (DMF); the amount ratio of BO to the organic solvent after the surface modification is 4 mg / mL;
[0019] The microwave power of the microwave solvothermal reaction in step 3) is 200-1000W, preferably 800W; the system pressure is 1-2MPa, preferably 1.2MPa; the reaction temperature is 160-200°C, preferably 180°C; and the reaction time is 5-40min, preferably 20min.
[0020] In step 3), after the microwave solvent thermal reaction is completed, centrifugation is performed at 6000-10000 rpm / min for 3-5 minutes, and the obtained product is washed three times with distilled water and then with anhydrous ethanol, and vacuum dried at 60° C. for 4-6 hours to obtain a bismuth trioxide / copper zinc tin sulfur composite photocatalyst, referred to as: BO / CZTS composite photocatalyst.
[0021] The bismuth trioxide / copper zinc tin sulfur composite photocatalyst provided by the present invention is prepared by the above method. The bismuth trioxide / copper zinc tin sulfur composite photocatalyst has a network structure, is formed by two nanosheet materials being interlaced and nested, and has a pore size between 50-100nm.
[0022] The present invention innovatively uses microwave solvothermal technology for the synthesis of δ-BO for the first time. Under the synergistic effect of microwave and high pressure, a two-dimensional network structure of BO is prepared. Then, CZTS with similar lattice parameters to δ-BO is constructed as the material for epitaxial growth. PVP is used to synthesize Cu 2+ The selective coordination of S 2- , and the microwave solvothermal reaction is used again to embed the generated CZTS nanosheets into the porous mesh BO. The construction of the two-dimensional / two-dimensional structure can not only provide a large number of free surface atoms to better participate in the interfacial catalytic reaction, but also provide a short transmission distance for the rapid migration of carriers from the inside to the surface, so that the material has a low intrinsic resistance. The present invention uses the microwave solvothermal method to synthesize the two-dimensional mesh BO, which not only improves the reaction efficiency, but also obtains a nano-network structure with uniform morphology. The microwave solvothermal method is further used to prepare the BO / CZTS composite photocatalyst, so that the CZTS nanosheets are embedded in the BO nano-mesh, which effectively improves the interface contact between the two materials, thereby improving the photocatalytic activity of the composite material.
[0023] The application of the bismuth trioxide / copper zinc tin sulfur composite photocatalyst provided by the invention in photodegradation is used for degradation of organic pollutants, especially for photocatalytic degradation of dyes.
[0024] Furthermore, the present invention prepares the BO / CZTS composite photocatalyst into BO / CZTS gel balls for use in degradation of organic pollutants.
[0025] The method for making BO / CZTS gel spheres is as follows:
[0026] S1, dispersing the above-prepared BO / CZTS composite photocatalyst, hydrogel carrier and NaHCO3 in deionized water, stirring and dispersing evenly to obtain a pre-gel solution;
[0027] S2. The pre-gel solution is dripped into the ZnCl2-CH3COOH aqueous solution through a syringe, and after being stirred and solidified, the pre-gel solution is taken out, washed, and freeze-dried to obtain BO / CZTS gel spheres.
[0028] In step S1, the concentration of the BO / CZTS composite photocatalyst in deionized water is 1-5 mg / mL, preferably 3 mg / mL; the mass ratio of the hydrogel carrier to the BO / CZTS composite photocatalyst is 10:1-5:1, preferably 7:1; the mass ratio of polyvinyl alcohol (PVA) to sodium alginate (SA) in the hydrogel carrier is 1:1-1:8, preferably 2:5; the mass ratio of NaHCO3 to SA is 1:2-2:1, preferably 1:1; stirring and dispersing uniformly means continuous stirring at 90°C for at least 1 hour;
[0029] In step S2, the volume ratio of the pregel solution to the ZnCl2-CH3COOH aqueous solution is 1:10; the syringe is without a needle and has a specification of 1-50mL, preferably 5mL, and the inner diameter of the liquid outlet is 0.1-0.5cm, preferably 0.2cm; the ZnCl2-CH3COOH mixed solution refers to ZnCl2 and CH3COOH mixed in water. The mass ratio of ZnCl2 to water is 1:18; the volume ratio of CH3COOH to water is 1:5-1:15, preferably 1:9.
[0030] In step S2, the pre-gel solution is dripped into the ZnCl2-CH3COOH mixed solution and then kept soaked for 2 hours to solidify the gel balls; taking out and cleaning means fully rinsing with distilled water at room temperature;
[0031] In step S2, the freeze drying means: after washing, transferring to a low-temperature freeze dryer, freeze drying at -30°C to -70°C for 12 hours, to obtain BO / CZTS gel spheres, referred to as SA / PVA-BO / CZTS;
[0032] Furthermore, the application method of SA / PVA-BO / CZTS is as follows: build a double-container photocatalytic reactor, place SA / PVA-BO / CZTS in one of the containers, add an organic pollutant solution, place it under a light source for degradation, and realize solution circulation through a peristaltic pump.
[0033] The double-container photocatalytic reactor of the present invention is composed of a 250mL perforated beaker, a 250mL conical flask and two peristaltic pumps. The beaker has an opening about 0.3cm from the bottom and 0.5cm from the top to connect the rubber tube and the peristaltic pump, and the flow rate of the peristaltic pump is controlled at 0-100mL / min. The liquid is pumped into the conical flask from the bottom of the perforated beaker, and the liquid in the conical flask is circulated to the perforated beaker by another peristaltic pump. When performing the photoreaction, the prepared SA / PVA-BO / CZTS is placed in the perforated beaker, the perforated beaker is placed under a xenon lamp, 150mL of rhodamine B is added to the perforated beaker and the conical flask, a magnetic stirring is added, and the peristaltic pump is turned on at the same time, and the rotation speed of the pump is controlled to make the solution flow rate constant.
[0034] In order to improve the actual performance of the catalyst, it is necessary to use a photoreactor. Currently, commercial photoreactors include two structures: suspension and film. The suspension structure has difficulties in catalyst separation and recovery, while the film structure has problems such as small reaction contact area and low solid-liquid mass transfer efficiency. The photoreactor used in the present invention uses gel balls as carriers to immobilize BO / CZTS composite photocatalysts, which effectively improves the problem of difficult catalyst separation and recovery in traditional suspension photoreactors. The SA / PVA semi-interpenetrating network gel carrier formed based on hydrogen bonds and ionic crosslinking not only improves the mechanical strength of the gel balls, but also effectively avoids catalyst seepage and catalytic performance attenuation; at the same time, the porous interconnected structure inside the gel balls helps to achieve high-concentration enrichment of organic matter and provide mass transfer channels, which is beneficial to the circulation of pollutants, thereby improving the problems of small reaction contact area and low solid-liquid mass transfer efficiency in film photoreactors.
[0035] The inventors found that the microwave solvothermal method is a method that combines the solvothermal method and the microwave method, taking into account the advantages of microwave and solvothermal. However, unlike the traditional solvothermal synthesis method, the microwave solvothermal method is no longer a single heat conduction method, but is heated by microwaves, so it has the characteristics of fast heating speed, sensitive reaction, uniform temperature of the heating system, etc., and can be used to quickly prepare nanomaterials with narrow particle size distribution and uniform morphology. The microwave solvent method can synthesize high-purity, fine-particle powders in a short time, avoiding the phenomenon that traditional heating easily leads to particle agglomeration. Therefore, the present invention uses the microwave solvothermal method to prepare two-dimensional network structure BO nanomaterials with uniform size and morphology.
[0036] In view of the problems of low light energy utilization rate and positive conduction band energy level of BO, in order to improve the light absorption ability and electron reduction ability, the present invention combines it with other narrow bandgap materials to form a heterojunction. The combination of wide bandgap metal oxides and narrow bandgap sulfides with matching energy bands can construct an effective built-in electric field, which helps to improve the separation ability of electrons and holes. CZTS is a quaternary sulfide semiconductor with non-toxic components, abundant sources and low prices. It is a direct bandgap semiconductor material with a bandgap width of 1.1-1.5eV, and its lattice constant has a high matching degree with δ-BO, which is conducive to epitaxial growth. Therefore, the present invention can simultaneously achieve the matching of energy bands and lattice constants by compounding CZTS and BO, which can not only broaden the light absorption range and improve the charge separation efficiency, but also help to build a close contact interface.
[0037] In response to the problem of photoreactor, the present invention embeds the powder photocatalyst in a transparent gel carrier to form a macroscopic large-sized gel ball as a photocatalyst, which can take into account the advantages of both. In order to improve the mechanical and mass transfer properties of the gel carrier, the control of the cross-linking degree and the pore size structure is the key. SA is a natural polysaccharide polymer, which is a copolymer composed of β-D-mannuronic acid and α-L-guluronic acid connected by β-1,4-glycosidic bonds. PVA is a water-soluble, non-toxic, biocompatible polymer. Because it contains a large number of hydroxyl groups, it can produce hydrogen bonds with the hydroxyl and carboxyl groups in the SA molecule, thereby forming a semi-interpenetrating network structure to increase the degree of cross-linking; in addition, the improvement of the mass transfer performance of the gel is achieved by constructing a porous interconnected structure through the acidification gas foaming method to synergistically enhance light absorption and pollutant diffusion.
[0038] Compared with the prior art, the present invention innovatively uses microwave solvent thermal synthesis of nano-network structure BO for the first time, and further uses microwave solvent thermal growth of CZTS nanosheets on the nano-network BO to construct a BO / CZTS composite photocatalyst, which not only improves light capture and increases charge separation, but also provides an effective charge transfer channel and improves photocatalytic activity. A semi-interpenetrating network structure hydrogel with SA / PVA as the skeleton is further constructed to immobilize the BO / CZTS composite photocatalyst and apply it to a photoreactor, effectively improving the difficulty of catalyst separation and recovery in a suspended photoreactor and the poor solid-liquid mass transfer efficiency in a thin film photoreactor. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is the SEM image of the BO / CZTS composite photocatalyst prepared in Example 1, and the illustrations a and b are BO and CZTS, respectively;
[0040] Figure 2 TEM (a), HRTEM (b) and EDS Mapping images (c) of the BO / CZTS composite photocatalyst prepared in Example 1;
[0041] Figure 3 XRD patterns of BO, CZTS and BO / CZTS composite photocatalysts prepared in Example 1;
[0042] Figure 4 The Raman images of BO, CZTS and BO / CZTS composite photocatalysts prepared in Example 1;
[0043] Figure 5 The XPS full spectrum (a), Bi 4f spectrum (b), O1s spectrum (c), Cu 2p spectrum (d), Zn 2p spectrum (e), Sn 3d spectrum (f), S2p spectrum (g) and S2s spectrum (h) of the BO / CZTS composite photocatalyst prepared in Example 1;
[0044] Figure 6 The fluorescence spectra (a), linear sweep voltammogram (b), transient photocurrent-time curve (c) and electrochemical impedance spectroscopy (d) of BO, CZTS and BO / CZTS composite photocatalysts prepared in Example 1 are shown in FIG.
[0045] Figure 7 The UV-visible diffuse reflectance spectra (a) of BO, CZTS and BO / CZTS composite photocatalysts prepared in Example 1 and the bandgap width (b) obtained according to the Tauc's plots method;
[0046] Figure 8 The concentration variation curves of photodegradation of Rhodamine B by BO, CZTS and BO / CZTS composite photocatalysts prepared in Example 1, wherein the blank refers to the self-decomposition curve of Rhodamine B;
[0047] Fig. 9 FT-IR image of SA / PVA-BO / CZTS prepared in Example 1;
[0048] Fig.10 The stress-strain curves of SA / PVA-BO / CZTS and SA-BO / CZTS prepared in Example 1;
[0049] Fig.11 SEM images of the surface (a) and interior (b) of SA / PVA-BO / CZTS prepared in Example 1;
[0050] Fig.12 The mercury entry and exit curves (a) and pore size distribution curves (b) of SA / PVA-BO / CZTS prepared in Example 1;
[0051] Fig.13 This is a structural diagram of the photoreactor used in Example 1;
[0052] Fig.14 The concentration change curve of PVA / SA-BO / CZTS prepared in Example 1 when repeatedly degrading RhB in a photodegradation reactor;
[0053] Fig.15 SEM images of BO (a) and BO / CZTS (b) prepared in Example 2;
[0054] Fig.16 XRD patterns of BO, CZTS and BO / CZTS prepared by the method of Example 2;
[0055] Fig.17The concentration variation curve of photodegradation of Rhodamine B by BO, CZTS and BO / CZTS prepared in Example 2;
[0056] Fig.18 SEM images of BO (a) and BO / CZTS (b) prepared in Comparative Example 1;
[0057] Fig.19 The concentration variation curve of photodegradation of Rhodamine B by BO, CZTS and BO / CZTS prepared in Comparative Example 1;
[0058] Fig. 20 This is the SEM image of BO / CZTS prepared in Comparative Example 2;
[0059] Fig.21 This is the concentration change curve of photodegraded Rhodamine B of BO, CZTS and BO / CZTS prepared in Comparative Example 2. DETAILED DESCRIPTION
[0060] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0061] Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources.
[0062] If no specific techniques or conditions are specified in the examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0063] Example 1
[0064] A preparation method of BO / CZTS composite photocatalyst is as follows:
[0065] 1) Add 24 mL of ethylene glycol and 48 mL of acetone to a 100 mL microwave reactor, then add 1.6 g of Bi(NO3)3·5H2O and mix well, then transfer the mixed solution to an autoclave and place it in a microwave reactor, and react for 20 min at a microwave power of 800 W, a system pressure of 2 MPa, a reaction temperature of 160° C., and a reaction time of 20 min. Centrifuge the obtained product at 10000 rpm for 3 min, wash the obtained product three times with distilled water, then wash it three times with anhydrous ethanol, and dry it in a vacuum oven at 60° C. for 6 h to obtain a porous mesh BO photocatalyst.
[0066] 2) 0.2 g of porous mesh BO was placed in 30 mL of aqueous solution, 100 μL of 3-mercaptopropionic acid was added, and the mixture was stirred at room temperature for 6 h, then centrifuged at 10000 rpm / min for 3 min, and washed once with water and once with DMF to obtain surface-modified BO for later use.
[0067] 3) 0.0109g CuCl2·2H2O, 0.2g PVP (MW = 44000-54000), 0.0043g ZnCl2, 0.0112g SnCl4·5H2O and 0.011g thiourea were added to 50mL DMF in sequence, stirred and dissolved, and then 0.2g surface-modified BO was added and stirred evenly. Then the mixed solution was transferred to an autoclave and placed in a microwave reactor. The reaction time was 20min at a microwave power of 800W, a system pressure of 1.2MPa, and a reaction temperature of 180°C. The obtained product was centrifuged at 10000rpm for 3min. The obtained product was first washed three times with distilled water, then washed three times with anhydrous ethanol, and dried in a vacuum oven at 60°C for 6h to obtain a BO / CZTS composite photocatalyst.
[0068] For comparison, the synthesis process of single CZTS is as follows: 0.6819g CuCl2·2H2O, 0.2g PVP, 0.2726g ZnCl2, 0.7012g SnCl4·5H2O and 0.6851g thiourea are added to 50mL DMF in sequence and stirred evenly. Then the mixed solution is transferred to an autoclave and placed in a microwave reactor. The reaction time is 20min at a microwave power of 800W, a system pressure of 1.2MPa, and a reaction temperature of 180℃. The obtained product is centrifuged at 10000rpm for 3min. The obtained product is first washed three times with distilled water, then washed three times with anhydrous ethanol, and dried in a vacuum oven at 60℃ for 6h to obtain a CZTS photocatalyst.
[0069] The application of the BO / CZTS composite photocatalyst prepared in Example 1 is specifically as follows:
[0070] S1. Take 30 mg of BO / CZTS powder and add it into 10 mL of water to fully disperse it to obtain a dispersion; add a mixture of 150 mg of SA, 60 mg of PVA (molecular weight of 1750±25) and 150 mg of NaHCO3 into the above dispersion, and continue stirring at 90°C for 1.5 hours to form a uniform pre-gel solution for standby use;
[0071] S2. Add 2.5g ZnCl2 and 5mL CH3COOH to 45mL water and stir evenly to obtain a ZnCl2-CH3COOH aqueous solution; take 5mL of the pre-gel solution and suck it into a syringe with an inner diameter of 0.2cm at the liquid outlet, and drip the prepared pre-gel solution drop by drop into the ZnCl2-CH3COOH solution through the syringe. After dripping, slowly stir at 1000rpm for 2h. After cross-linking and pore formation, take out the formed gel balls, rinse the surface of the gel balls with distilled water to remove the ZnCl2 and CH3COOH attached to the surface, and then transfer them to a low-temperature freeze dryer and freeze-dry them at -60°C for 12h to obtain the composite photocatalyst gel balls SA / PVA-BO / CZTS.
[0072] S3. Use PVA / SA-BO / CZTS as a catalyst to build a photodegradation reactor, as follows: The reactor consists of a 250mL perforated beaker, a 250mL conical flask and two peristaltic pumps. Among them, the beaker has an opening at about 0.3cm from the bottom and 0.5cm from the top to connect the rubber tube and the peristaltic pump, and the flow rate of the peristaltic pump is controlled at 0-100mL / min. The liquid is pumped into the conical flask from the bottom of the perforated beaker, and the liquid in the conical flask is circulated to the perforated beaker by another peristaltic pump. When the photoreaction is carried out, the prepared PVA / SA-BO / CZTS is placed in the perforated beaker, the beaker is placed under a xenon lamp, 150mL of rhodamine B is added to the perforated beaker and the conical flask, and a magnetic stirring is added. At the same time, the peristaltic pump is turned on and the speed of the pump is controlled to keep the solution flow rate constant.
[0073] As a comparison, SA-BO / CZTS gel spheres immobilized using only SA as a carrier were prepared. The preparation method is as follows:
[0074] S1. Take 30 mg of BO / CZTS powder and add it to 10 mL of water. After fully dispersing, obtain a dispersion. Add a mixture of 150 mg of SA and 150 mg of NaHCO3 to the dispersion. Stir well for 1.5 h at room temperature to form a uniform pre-gel solution for use.
[0075] S2. Add 2.5g ZnCl2 and 5mL CH3COOH to 45mL water and stir evenly to obtain ZnCl2-CH3COOH solution. Take 5mL pre-gel solution and suck it into a syringe with an inner diameter of 0.2cm at the outlet. Add the prepared pre-gel solution drop by drop into the ZnCl2-CH3COOH solution through the syringe. After dripping, slowly stir at 1000rpm for 2h. After cross-linking and pore formation, take out the formed gel ball, rinse the surface of the gel ball with distilled water to remove the ZnCl2 and CH3COOH attached to the surface, and then transfer it to a low-temperature freeze dryer and freeze-dry it at -60℃ for 12h to obtain SA-BO / CZTS.
[0076] For tensile testing, SA / PVA-BO / CZTS (film) and SA-BO / CZTS (film) were prepared.
[0077] SA / PVA-BO / CZTS (film) was prepared as follows: 30 mg of BO / CZTS powder was added to 10 mL of water and fully dispersed to obtain a dispersion, 150 mg of SA, 60 mg of PVA (molecular weight 1750±25) and 150 mg of NaHCO3 were added to the dispersion, and stirred at 90°C for 1.5 h to form a uniform pre-gel solution for use. At the same time, 2.5 g of ZnCl2 and 5 mL of CH3COOH were added to 45 mL of water and stirred evenly to obtain a ZnCl2-CH3COOH solution. The prepared pre-gel solution was placed in a container with a size of 5cm×5cm×5cm, frozen at -20℃ for 6h to solidify, then placed in a ZnCl2-CH3COOH solution and slowly stirred for 2h. After cross-linking and pore formation, the formed gel membrane was taken out, and the gel membrane was thoroughly rinsed with distilled water to remove the ZnCl2 and CH3COOH attached to its surface, and then transferred to a low-temperature freeze dryer and freeze-dried at -60℃ for 12h to obtain SA / PVA-BO / CZTS (membrane).
[0078] The preparation of SA-BO / CZTS (film) is as follows: 30 mg of BO / CZTS powder is added to 10 mL of water, and the dispersion is obtained after being fully dispersed. A mixture of 150 mg of SA and 150 mg of NaHCO3 is added to the above dispersion, and a uniform pre-gel solution is formed after being fully stirred at room temperature for 1.5 hours, and then it is set aside. At the same time, 2.5 g of ZnCl2 and 5 mL of CH3COOH are added to 45 mL of water, and stirred evenly to obtain a ZnCl2-CH3COOH solution. The prepared pre-gel solution is poured into a container with a size of 5 cm × 5 cm × 5 cm, frozen at -20 ° C for 6 hours to solidify, and then placed in a ZnCl2-CH3COOH solution, slowly stirred for 2 hours, and after it is cross-linked and pore-formed, the formed gel film is taken out, and the gel film is fully rinsed with distilled water to remove the ZnCl2 and CH3COOH attached to its surface, and then transferred to a low-temperature freeze dryer and freeze-dried at -60 ° C for 12 hours to obtain SA-BO / CZTS (film).
[0079] Figure 1is a SEM photo of BO / CZTS prepared in Example 1. From the figure, it can be seen that the catalyst is a two-dimensional network structure formed by the interlaced nesting and stacking of BO nanosheets and CZTS nanosheets. In the illustration, a is a SEM photo of BO. It can be seen that BO is a network structure composed of nanosheets with a hole diameter of 50-100nm and a nanosheet thickness of 20-30nm. The CZTS in the illustration b is a flower-like structure assembled from nanosheets with a thickness of about 40-50nm and a diameter of about 500nm. It can be seen that the structure of BO / CZTS is based on the network BO, and the CZTS nanosheets are embedded in it and stacked and grown, indicating the successful composite of the two materials CZTS and BO.
[0080] Figure 2 is the TEM photo and element mapping of BO / CZTS prepared in Example 1. Figure 2 In a, we can see that the composite photocatalyst is assembled by stacking nanosheets. HETEM ( Figure 2 In (b), the lattice fringes with a lattice spacing of 0.192 nm correspond to the (220) crystal plane of CZTS, and the lattice spacing of 0.326 nm can be identified as the (111) crystal plane of BO, while the staggered lattice fringes originate from the stacked and nested parts of BO and CZTS nanosheets (green dotted area). Figure 2 Figure c is the EDS spectrum of BO / CZTS, which confirms that the composite material is composed of Cu, Zn, Sn, S, Bi and O elements, and the two materials are evenly distributed, further confirming the close combination of the two.
[0081] Figure 3 The XRD spectra of BO, CZTS and BO / CZTS prepared in Example 1 are shown in Figure 1. The XRD peaks at 27.95°, 32.39°, 46.45° and 55.08° in the BO spectrum correspond to the (111), (200), (220) and (311) crystal planes, which are consistent with the cubic phase δ-BO spectrum (JCPDS No.27-0052); the XRD peaks at 28.28°, 32.86°, 47.28° and 56.22° in the CZTS spectrum correspond to the (112), (200), (220) and (312) crystal planes of CZTS, which are consistent with the standard spectrum of CZTS with tetragonal kesterite structure (JCPDS No.26-0575). The diffraction peaks of the above two materials appear in the spectrum of BO / CZTS, indicating the successful construction of the composite material.
[0082] Figure 4 The Raman spectra of BO, CZTS and BO / CZTS prepared in Example 1 are shown in Figure 1. The 399 cm -1 , 521cm -1 and 640cm -1The Raman peaks at 640 cm -1 The peak at 288 cm is the characteristic peak of δ-BO; while the peak at 288 cm -1 and 333cm -1 The two characteristic peaks of the A symmetric mode appearing at derive from the tetragonal kesterite phase structure. All these peaks are visible in BO / CZTS, but the peak positions are shifted to a certain extent, indicating that there is a strong chemical coupling between the two (defect-free lateral connection force), which further confirms the successful composite of BO and CZTS.
[0083] Figure 5 is the XPS graph of BO / CZTS prepared in Example 1. Figure 5 As can be seen from a, it contains elements such as Cu, S, Zn, O, Bi, Sn, and C, among which C comes from the residue of carbon-containing organic matter; Figure 5 Where b is the Bi spectrum, which is split into Bi 4f 5 / 2 (164.0eV) and Bi4f 7 / 2 (158.7eV), the splitting energy difference is 5.3eV, indicating that Bi exists in the +3 valence form; Figure 5 c is the O spectrum, the peak at 529.45 eV corresponds to the Bi-O bond in, and the peak at 530.75 eV corresponds to the oxygen vacancies on the δ-BO surface (OV); Figure 5 The d in the figure is the Cu spectrum, with the core level split into Cu 2p 1 / 2 (951.6 eV) and Cu 2p 3 / 2 (931.7eV), the splitting energy difference is 19.9eV, confirming that Cu + existence; Figure 5 where e is the Zn spectrum, which is split into Zn 2p 1 / 2 (1044.7 eV) and Zn 2p 3 / 2 (1021.7eV), the splitting energy difference is 23eV, indicating that Zn has a valence of +2; Figure 5 f is the Sn spectrum, and the two peaks centered at 494.4 eV and 485.95 eV correspond to the Sn 3d 3 / 2 and Sn 3d 5 / 2 , and its splitting energy difference is 8.45 eV, confirming that the Sn element is in the Sn 4+ state; Figure 5 The S2p peak at 162.3 eV in the middle g is consistent with the Bi 4f 5 / 2 The peaks are very close, proving that S 2- The existence of; In addition, the 2s spectrum of S ( Figure 5 (h) shows an obvious peak at 225.1 eV, confirming the existence of Bi-S bonds and indicating the successful recombination of BO and CZTS.
[0084] Figure 6 Figures ad are the fluorescence spectra (PL), linear sweep voltammetry (LSV), transient photocurrent-time (It) curves and electrochemical impedance spectroscopy (EIS) of BO, CZTS and BO / CZTS prepared in Example 1. The PL spectrum shows that the emission peak of BO is located at 425nm, corresponding to the band gap transition; while the emission peak of CZTS is located at 423nm and 467nm, corresponding to the recombination of sulfur vacancies and zinc vacancies, respectively; in comparison, BO / CZTS has the lowest fluorescence intensity, indicating that the electron-hole recombination rate in the composite material is low, which is conducive to charge separation. LSV shows that BO / CZTS has the highest photocurrent density and the lowest starting potential, indicating that the composite material has a low Fermi level and high charge separation ability. The It curve shows that BO / CZTS has the largest photocurrent, which is about 4 times that of CZTS and 2 times that of BO, further confirming that the construction of the composite material is conducive to charge separation. EIS shows that BO / CZTS has the smallest Nyquist semicircle diameter, which means it has the lowest charge transfer resistance, indicating that the charge transfer rate from the photocatalyst to the photoelectrode is the fastest. The equivalent circuit is drawn by ZView fitting ( Figure 6 (Inset in center (d)) The resistances of BO, CZTS and BO / CZTS were 108070Ω, 27419Ω and 8814Ω, respectively.
[0085] Figure 7 Figure a is the UV-visible diffuse reflectance spectra (DRS) of BO, CZTS and BO / CZTS prepared in Example 1. It can be seen from the figure that single BO exhibits a significant light response near 400nm, while the absorption sideband of the BO / CZTS composite photocatalyst is significantly red-shifted to near 500nm, with higher absorption in the visible light region. Figure 7 b is the bandgap width of the material obtained by Tauc's plots method. The band gaps of BO, CZTS and BO / CZTS are 3.42eV, 1.55eV and 3.15eV respectively. Obviously, the construction of BO / CZTS effectively broadens the absorption spectrum of the material and reduces the band gap.
[0086] Figure 8 The photodegradation performance curve of BO, CZTS and BO / CZTS prepared in Example 1 for Rhodamine B (RhB). The photodegradation experiment was carried out according to the following steps: 30 mg of the synthesized BO, CZTS and BO / CZTS were suspended in 50 mL of a 60 mg / L RhB solution. Stir and ultrasonicate for 10 minutes to obtain a homogeneous dispersion. Take out 2 mL of the suspension from the system at regular intervals, centrifuge to remove solid particles, and use a UV-visible spectrophotometer to detect the maximum absorbance change of RhB (λ=554 nm). With the reaction time as the horizontal axis, the absorbance value (Ct ) and the absorbance of the system before the reaction (C0) were plotted as the ordinate. Before photodegradation, the suspension was placed in the dark for 30 min to reach adsorption-desorption equilibrium. The photoreaction was carried out under AM1.5 sunlight emitted by a 300W xenon lamp equipped with a CUT420 filter. The adsorption rate and degradation rate were calculated by the ratio of (C0-C0) under dark reaction and photoreaction, respectively. t The distance between the xenon lamp and the reaction pool is 10 cm, and the light source intensity is about 220 mW / cm 2 . To prevent the temperature from rising, the system is cooled with circulating water. As can be seen from the figure, RhB will not self-decompose (blank curve), and the adsorption rates of BO, CZTS and BO / CZTS in the dark reaction for 30 minutes are 6.2%, 7.14% and 56.55%, respectively. After 30 minutes of illumination, BO and CZTS are not degraded, and the degradation rate of BO / CZTS is 99.99%. It can be seen that single CZTS and BO can only adsorb a small amount of RhB, and have no obvious photocatalytic decomposition ability, while BO / CZTS has a significant catalytic decomposition effect on organic pollutants.
[0087] Fig. 9 This is the diffuse reflectance infrared spectrum of the SA / PVA-BO / CZTS gel sphere prepared in Example 1. 3461cm -1 、2917cm -1 、1635cm -1 and 1417cm -1 The peaks corresponding to the stretching vibration of OH in SA, the stretching vibration of CH, the asymmetric stretching vibration of C=O in the carboxyl group, and the symmetric stretching vibration of C=O, 1034 cm -1 This corresponds to the stretching vibration peak of CO. 3411cm -1 、2912cm -1 、1432cm -1 and 1093cm -1 The peaks at 1644 cm-1 are the OH stretching vibration, CH stretching vibration, OH bending vibration and CO stretching vibration peaks in PVA. In comparison, the C=O asymmetric stretching vibration in the carboxyl group in SA / PVA-BO / CZTS is blue-shifted to 1644 cm-1. -1 The high wave number of -OH stretching vibration peak is 3457cm -1 narrowed, indicating that hydrogen bonds were formed between SA and PVA. -1 The characteristic peaks observed nearby are attributed to the stretching vibration of Bi-O bonds, confirming that BO / CZTS is encapsulated by gel spheres.
[0088] Fig.10The stress-strain curves of SA / PVA-BO / CZTS (film) and SA-BO / CZTS (film) prepared in Example 1. It can be clearly seen from the figure that in the initial stage of stretching, the tensile curve is close to linear. As the tensile tester moves, the stress continues to increase, and then the curve begins to show obvious nonlinear characteristics. When the stress increases to a certain extent, the gel film breaks, and the tensile stress level decreases rapidly. The fracture stress of SA / PVA-BO / CZTS (film) is 921kPa, and the elongation at break is 19.74%; while the fracture stress of SA-BO / CZTS (film) is only 267kPa, and the elongation at break is 10.35%. It can be seen that the addition of PVA improves the tensile properties of the SA film by about 3.5 times, and the elongation is also doubled, indicating that the addition of PVA significantly improves the mechanical properties of the hydrogel.
[0089] Fig.11 This is the morphology of SA / PVA-BO / CZTS prepared in Example 1. Fig.11 Figure a is a SEM image of the surface of the gel ball. It can be seen from the figure that the surface of the gel ball has a large number of shallow closed pores with a size of 10-20 μm, which not only increases its specific surface area but also facilitates the enrichment of pollutants. Fig.11 Figure b shows the internal morphology of the gel sphere. It can be seen that it has a large number of open pores with a size of 500nm-1μm, which can provide mass transfer channels for the photocatalytic reaction and facilitate the transmission of pollutants.
[0090] Fig.12 The mercury injection curve and pore size distribution diagram of SA / PVA-BO / CZTS prepared in Example 1. Fig.12 The a in the figure is the mercury injection and mercury removal curve. The mercury removal amount is about 1 / 3 of the mercury injection amount, indicating that the pores inside the material have a certain degree of connectivity. Fig.12 Middle (b) shows that the pore size distribution of SA / PVA-BO / CZTS is mostly in the range of 1-30 μm and is relatively uniform, which provides an effective way for the enrichment and transportation of pollutants.
[0091] Fig.13The photoreactor physical diagram used in Example 1. The reactor is composed of a 250mL perforated beaker, a 250mL conical flask and two peristaltic pumps. Wherein, the beaker has a perforation at about 0.3cm from the bottom and 0.5cm from the top to connect a rubber tube and a peristaltic pump, and the peristaltic pump flow rate is controlled at 0-100mL / min. Liquid is pumped into the conical flask from the bottom of the perforated beaker, and the liquid in the conical flask is circulated to the perforated beaker by another peristaltic pump. When carrying out the photoreaction, the prepared PVA / SA-BO / CZTS is placed in the perforated beaker, the beaker is placed under a xenon lamp, 150mL of rhodamine B is added to the perforated beaker and the conical flask, magnetic stirring is added, and the peristaltic pump is turned on at the same time to control the rotating speed of the pump so that the solution flow rate is constant.
[0092] Fig.14 This is the performance curve of SA / PVA-BO / CZTS for repeated degradation of RhB in a photodegradation reactor. The degradation experiment was carried out according to the following steps: the prepared gel balls were placed in an open-hole beaker, and 150 mL of Rhodamine B (concentration of 60 mg / L) solution was added to the open-hole beaker and the conical flask. The circulation pump was turned on to keep the flow rate of the inlet and outlet solutions consistent. A certain amount of degradation solution was taken every 10 minutes, and the change in the maximum absorbance of RhB (λ = 554 nm) was detected by a UV-visible spectrophotometer. With the reaction time as the horizontal axis, the absorbance value (C t ) and the absorbance of the system before the reaction (C0) were plotted as the ordinate. Before photodegradation, it was placed in the dark for 30 minutes to reach adsorption-desorption equilibrium. The photoreaction was carried out under AM1.5 sunlight emitted by a 300W xenon lamp equipped with a CUT420 filter. The adsorption rate and degradation rate were respectively calculated by the ratio of (C0-C0) under dark reaction and photoreaction. t The distance between the xenon lamp and the reaction pool is 10 cm, and the light source intensity is about 220 mW / cm 2 To prevent the temperature from rising, the system was cooled with circulating water. The reusability experiment was achieved by soaking the gel balls in distilled water for 1-3 hours after each photodegradation to remove the dye molecules adsorbed on the surface and freeze-drying them before performing the photodegradation reaction again.
[0093] From the inset of the vial in the figure, it can be seen that the original RhB solution is a dark rose red. During the dark adsorption process, its color does not change significantly. As the illumination time increases, the color of the RhB solution gradually fades and becomes almost colorless after 90 minutes of illumination, which proves that the RhB molecules are effectively decomposed. Furthermore, the three degradation rates under illumination are 93.85%, 87.78% and 82.16% respectively (the adsorption rates of the dark reaction for 30 minutes are 23.42%, 20.48% and 18.08% respectively). Obviously, the photoreactor has good reusability.
[0094] Example 2
[0095] A preparation of a BO / CZTS composite photocatalyst, changing the synthesis temperature of BO, is as follows:
[0096] 1) Add 24 mL of ethylene glycol and 48 mL of acetone to a 100 mL autoclave, and finally add 1.6 g of Bi(NO3)·5H2O and mix well. Then transfer the mixed solution to a microwave reactor, react for 20 min at a microwave power of 800 W, a system pressure of 2 MPa, and a reaction temperature of 140° C., centrifuge the obtained product at 10,000 rpm for 3 min, wash the obtained product three times with distilled water, then wash it three times with anhydrous ethanol, and dry it in a vacuum oven at 60° C. for 6 h to obtain BO powder;
[0097] 2) 0.2 g of BO powder was placed in 30 mL of aqueous solution, 100 μL of 3-mercaptopropionic acid was added, and the mixture was stirred at room temperature for 6 h, then centrifuged at 10,000 rpm / min for 3 min, and washed once with water and once with DMF for later use to obtain surface-modified BO.
[0098] 3) 0.0109g CuCl2·2H2O, 0.2g PVP, 0.0043g ZnCl2, 0.0112g SnCl4·5H2O and 0.011g thiourea were added to 50mL DMF in sequence, stirred and dissolved, and then 0.2g surface-modified BO was added and stirred evenly. Then the mixed solution was transferred to a high-pressure reactor and placed in a microwave reactor. The microwave power was 800W, the system pressure was 1.2MPa, and the reaction temperature was 180°C for 20min. The obtained product was centrifuged at 10000rpm for 3min. The obtained product was first washed three times with distilled water, then washed three times with anhydrous ethanol, and dried in a vacuum oven at 60°C for 6h to obtain BO / CZTS.
[0099] For comparison, the synthesis process of a single CZTS is as follows: the same as the synthesis process of a single CZTS in Example 1.
[0100] Fig.15 The SEM images of BO and BO / CZTS prepared by the method of Example 2 are shown in FIG. Fig.15 As can be seen in a, the prepared BO has a network structure composed of nanosheets with a pore size between 50-100nm and a nanosheet thickness of about 20-30nm. Fig.15 Figure b shows the surface morphology of BO / CZTS, where the two nanosheets can be stacked to form a network structure. It can be seen that changing the reaction temperature has little effect on the morphology of either BO or BO / CZTS.
[0101] Fig.16The XRD patterns of BO, CZTS and BO / CZTS prepared by the method of Example 2. As can be seen from the figure, the characteristic peaks of BO and CZTS correspond to JCPDS No. 27-0052 and JCPDS No. 26-0575, respectively, and the characteristic peaks of BO and CZTS can be seen on BO / CZTS, indicating that the temperature change does not change the crystal phase structure of BO and CZTS and the assembly is successful.
[0102] Fig.17 The photodegradation performance curves of BO, CZTS and BO / CZTS prepared by the method of Example 2 for RhB are shown in Table 1. Figure 8 The degradation method is the same. As can be seen from the figure, the adsorption rates of BO, CZTS and BO / CZTS after 30 minutes of dark reaction are 6.86%, 7.14% and 56.05% respectively. After 30 minutes of light exposure, BO and CZTS are not degraded, and the degradation rate of BO / CZTS is 99.99%. It can be seen that the adsorption and degradation data of BO / CZTS are similar to those in Example 1. Figure 8 The degradation data are close. Therefore, changing the synthesis temperature of BO to 140 °C still has a similar effect.
[0103] Comparative Example 1
[0104] A preparation of BO / CZTS, BO and BO / CZTS are both prepared by a solvothermal method, specifically:
[0105] 1) 1.6 g Bi(NO3)·5H2O was added to 24 mL ethylene glycol and 48 mL acetone and mixed well. The mixed solution was then transferred to a high-pressure reactor and reacted in a 160° C. forced air drying oven for 6 h. The obtained product was centrifuged at 10000 rpm for 3 min, washed three times with distilled water, then washed three times with anhydrous ethanol, and dried in a 60° C. vacuum oven for 6 h to obtain BO.
[0106] 2) 0.2 g of BO was placed in 30 mL of aqueous solution, 100 μL of 3-mercaptopropionic acid was added, and the mixture was stirred at room temperature for 6 h, then centrifuged at 10,000 rpm / min for 3 min, and washed once with water and once with DMF to obtain surface-modified BO.
[0107] 3) 0.0109g CuCl2·2H2O, 0.2g PVP, 0.0043g ZnCl2, 0.0112g SnCl4·5H2O and 0.011g thiourea were added to 50mL DMF in sequence, stirred and dissolved, and then 0.2g surface-modified BO was added and stirred evenly. Then the mixed solution was transferred to a 100mL autoclave, reacted at 180°C in a forced air drying oven for 24h, cooled to room temperature, and the obtained product was centrifuged at 10000rpm for 3min. The obtained product was first washed three times with distilled water, then washed three times with anhydrous ethanol, and dried in a vacuum oven at 60°C for 6h to obtain BO / CZTS.
[0108] For comparison, the synthesis process of single CZTS is as follows: 0.6819g CuCl2·2H2O, 0.2g PVP, 0.2726g ZnCl2, 0.7012g SnCl4·5H2O and 0.6851g thiourea are added to 50mL DMF in sequence and stirred evenly. Then the mixed solution is transferred to a 100mL autoclave, reacted at 180°C in a forced air drying oven for 24h, cooled to room temperature, centrifuged at 10000rpm for 3min, washed three times with distilled water, then washed three times with anhydrous ethanol, and dried in a vacuum oven at 60°C for 6h to obtain a CZTS photocatalyst.
[0109] Fig.18 BO( Fig.18 a) and BO / CZTS( Fig.18 SEM image of (b) in the middle. It can be seen that BO presents a block structure of varying sizes, while BO / CZTS presents a morphology of disordered accumulation of nanoparticles. Therefore, the solvothermal method cannot form a two-dimensional network structure in which the two nanosheets are nested with each other.
[0110] Fig.19 The photodegradation performance curve of BO / CZTS prepared in Comparative Example 1 to RhB is shown in FIG. Figure 8 The degradation method is the same. As can be seen from the figure, the adsorption rate of BO / CZTS in the dark reaction for 30 minutes is only 1.26%, which is even lower than that of single BO and CZTS. It is completely undegraded under light for 30 minutes. Compared with the composite photocatalyst prepared in Example 1, its degradation effect is significantly worse. This shows that the material structure has an important influence on the photocatalytic performance.
[0111] Comparative Example 2
[0112] A preparation method of BO / CZTS material, wherein CZTS is prepared by a solvothermal method, specifically:
[0113] 1) 24 mL of ethylene glycol and 48 mL of acetone were added to a 100 mL microwave reactor, and finally 1.6 g of Bi(NO3)3·5H2O was added and mixed evenly, and then the mixed solution was transferred to an autoclave and placed in a microwave reactor, and the reaction was carried out for 20 min at a microwave power of 800 W, a system pressure of 2 MPa, and a reaction temperature of 160°C. The obtained product was centrifuged at 10000 rpm for 3 min, and the obtained product was first washed three times with distilled water, then washed three times with anhydrous ethanol, and dried in a vacuum oven at 60°C for 6 h to obtain a porous mesh BO.
[0114] 2) 0.2 g of porous mesh BO was placed in 30 mL of aqueous solution, 100 μL of 3-mercaptopropionic acid was added, and the mixture was stirred at room temperature for 6 h, then centrifuged at 10,000 rpm / min for 3 min, and washed once with water and once with DMF to obtain surface-modified BO for later use.
[0115] 3) 0.0109g CuCl2·2H2O, 0.2g PVP, 0.0043g ZnCl2, 0.0112g SnCl4·5H2O and 0.011g thiourea were added to 50mL DMF in sequence, stirred and dissolved, and then 0.2g surface-modified BO was added and stirred evenly. Then the mixed solution was transferred to a 100mL autoclave, reacted at 180°C in a forced air drying oven for 24h, cooled to room temperature, and the obtained product was centrifuged at 10000rpm for 3min. The obtained product was first washed three times with distilled water, then washed three times with anhydrous ethanol, and dried in a vacuum oven at 60°C for 6h to obtain BO / CZTS.
[0116] For comparison, the synthesis process of a single CZTS is as follows: the same as the synthesis process of a single CZTS in Comparative Example 1.
[0117] Fig. 20 The SEM image of BO / CZTS prepared in Comparative Example 2. After a long period of solvothermal reaction, the surface of the porous mesh BO prepared by the microwave solvothermal method is no longer flat, and some nanosheets melt and transform into a solid structure, while CZTS nanoparticles are randomly accumulated on the BO surface. Therefore, the solvothermal reaction cannot form a two-dimensional mesh structure in which two nanosheets are nested with each other.
[0118] Fig.21 The photodegradation performance curve of BO / CZTS prepared in Comparative Example 2 to RhB is shown in FIG. Figure 8 The degradation method is the same. As can be seen from the figure, the adsorption rate of BO / CZTS after 30 minutes of dark reaction is 26.40%, and it is almost not degraded under light for 30 minutes. Compared with the BO / CZTS prepared in Example 1, its degradation effect is significantly worse. This once again confirms that the material structure has an important influence on the photocatalytic performance.
[0119] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.
Claims
1. A method for preparing a bismuth trioxide / copper zinc tin sulfur composite photocatalyst, characterized in that: The preparation method comprises the following steps: 1) Preparation of porous network BO by microwave solvothermal reaction; 2) Modification of porous mesh BO by surface modifier; 3) adding a copper source and a ligand into an organic solvent, then adding a zinc source, a tin source and a sulfur source, stirring evenly, and finally adding the surface-modified BO, transferring the obtained mixed dispersion into an autoclave for microwave solvent thermal reaction, and then washing and drying to obtain a BO / CZTS composite photocatalyst.
2. The preparation method according to claim 1, characterized in that: In step 1), the method for preparing porous mesh BO by microwave solvothermal method is: The bismuth salt is dissolved in an organic solvent and stirred evenly; the obtained mixed solution is transferred to an autoclave for microwave solvent thermal reaction, and then washed and dried to obtain a porous mesh BO.
3. The preparation method according to claim 2, characterized in that: In step 1), the organic solvent is a mixed solution of ethylene glycol and acetone; the volume ratio of ethylene glycol to acetone is 1:2; the microwave power of the microwave solvent thermal reaction is 200-1000W, the system pressure is 2-3MPa, the reaction temperature is 140-180°C, and the reaction time is 5-40min.
4. The preparation method according to claim 1, characterized in that: In step 2), the surface modification of the porous mesh BO is specifically: the porous mesh BO is dispersed in deionized water, a surface modifier is added, stirred, and washed to obtain the surface modified BO.
5. The preparation method according to claim 4, characterized in that: In step 2), the surface modifier is selected from ethanethiol, 2-mercaptoacetic acid, and 3-mercaptopropionic acid; the amount ratio of the surface modifier to deionized water is 1-10 μL / mL.
6. The preparation method according to claim 1, characterized in that: In step 3), the molar ratio of the copper source, zinc source, tin source and sulfur source is 5-8:2-5:2-5:15-20; the mass of the complexing agent is 15-20 times the mass of the copper salt; the complexing agent is polyvinyl pyrrolidone, and the organic solvent is N,N-dimethylformamide.
7. The preparation method according to claim 1 or 6, characterized in that: In step 3), the microwave power of the microwave solvent thermal reaction is 200-1000W, the system pressure is 1-2MPa, the reaction temperature is 160-200°C, and the reaction time is 5-40min.
8. A bismuth trioxide / copper zinc tin sulfur composite photocatalyst prepared by the preparation method according to any one of claims 1 to 7, characterized in that: The bismuth trioxide / copper zinc tin sulfur composite photocatalyst has a network structure, which is formed by staggered stacking of two material nanosheets, and the pore size is between 50-100nm.
9. An application of the bismuth trioxide / copper zinc tin sulfur composite photocatalyst according to claim 8, characterized in that: Used for photodegradation of organic pollutants.
10. The use according to claim 9, characterized in that: The bismuth trioxide / copper zinc tin sulfur composite photocatalyst is made into BO / CZTS gel balls for organic pollutant degradation. The method for making the BO / CZTS gel balls is as follows: S1, dispersing the above-prepared BO / CZTS composite photocatalyst, hydrogel carrier and NaHCO3 in deionized water, stirring and dispersing evenly to obtain a pre-gel solution; S2. The pre-gel solution is dripped into the ZnCl2-CH3COOH aqueous solution through a syringe, and after being stirred and solidified, the pre-gel solution is taken out, washed, and freeze-dried to obtain BO / CZTS gel spheres.